CHANGE IN THE PROFESSIONALISM OF TEACHERS IN THE GLOBALIZATION ERA: OPPORTUNITIES AND CHALLENGES - Yadi Suryadi; Yasin Muhammad Syibli; Muhammad Khoiri; Eduar Baene; Moh. Imron Rosidi (Adisam Publisher, 2024)
Education is the most important element for the advancement of a nation's civilization. The industrial era and globalization have had an impact on educational processes, in Indonesia. On the one hand, globalization has the positive impact of facilitating access to information, but on the other hand, the dominance of technology has the negative impact of dehumanizing a mentality that places technology above everything else. In fact, education in the modern era of globalization is experiencing a value crisis. Education only produces cognitively intelligent outputs, mastering theory and technology but lacking in human and social values. (dehumanisasi). As a solution, education as an investment must be capable of “humanizing man”; integrating man and techno or integrating science and religion, as well as re-paradigmatizing education with a value approach, a sociocultural approach, an approach to cognitive skills, and a policy approach, which is of course necessary to the goal of national education to form a professional education. A generation of moral, responsible, and dignified.